Heat Treatment Effect on Some Mechanical Properties of FDM-Manufactured PCL Wood-Based Biopolymer - Irina Beșliu-Băncescu; Ioan Tamașag (Advances in Polymer Technology)
The study investigates some 3D printing output parameters of a polycaprolactone (PCL) wood-based biopolymer, a category of materials obtained by embedding wood-derived components within polymeric matrices. These wood-based biopolymers have garnered significant focus in recent years due to their environmental friendliness and vast potential across many different fields. A full factorial design with three independent variables (layer height, printing speed, and heat treatment exposure time) at three levels was considered. The research explores printing speeds higher than the speed ranges typically investigated in the existing scientific literature on FDM 3D printing of wood-based polymers. Additionally, in this study, heat treatment is proposed as a post-processing operation to enhance certain crucial proprieties such as surface quality, hardness, mechanical strength, and accuracy. The findings reveal that heat treatment has a positive influence on the investigated output parameters. Notably, 3D printed samples subjected to heat treatment exhibit an average decrease of 112.1% in surface roughness for a 5-min exposure time and 121.73% for a 10-min exposure time. The surface hardness of the samples also improved after applying the heat treatment. The part hardness improved with an average of 0.65%. Furthermore, significant correlations were observed between layer height and surface quality, hardness, printing speed, and tensile strength. Notably, printing speed contributed significantly to the variation in tensile strength, accounting for 52.77% of the parameter’s variation. These insights shed light on the optimization of 3D printing processes for wood-based biopolymers, paving the way for enhanced performance and applicability across diverse fields.